2016
DOI: 10.1021/acs.orglett.6b02282
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structures and Molecular Associations of a Peptide-Based Catalyst for the Stereoselective Baeyer–Villiger Oxidation

Abstract: The structural analysis of a peptide-based catalyst for the Baeyer-Villiger oxidation (BVO) is reported. This unique structure is then analyzed in the context of its previously documented facility to control selectivity (both enantioselectivity and migratory aptitude) in catalytic reactions. The effects of additives on the solution conformation of the peptide are found to be dramatic, revealing substrate-specific interactions and a possible “induced fit” model. The experimental observation of dynamic behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…14 In the case of 2 -catalyzed BVO, a favorable interaction of the amido group with catalyst 2 is consistent with our recent observations (Figure 2b). This hypothesis was stimulated by analysis of an experimentally derived (ROESY) solution structure of 2 , 26 along with our study of catalyst analogues. 15 A critical role for the lysine side chain, along with the schematic secondary structure shown, contributes to a view of competing hydrogen bonding networks as catalyst ent - 2 operates on substrate 14 - trans (Figure 2c).…”
Section: Results and Discussionmentioning
confidence: 99%
“…14 In the case of 2 -catalyzed BVO, a favorable interaction of the amido group with catalyst 2 is consistent with our recent observations (Figure 2b). This hypothesis was stimulated by analysis of an experimentally derived (ROESY) solution structure of 2 , 26 along with our study of catalyst analogues. 15 A critical role for the lysine side chain, along with the schematic secondary structure shown, contributes to a view of competing hydrogen bonding networks as catalyst ent - 2 operates on substrate 14 - trans (Figure 2c).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In general, α-peptides of small or medium size (3–20 residues) are conformationally flexible and able to adopt several conformers that are in rapid equilibrium unless constraints are implemented . Recent studies by Miller as well as Thiele and Schreiner showed that even peptidic catalysts with rigidifying turn motifs adopt more than one structure but can be highly stereoselective. Despite these examples, there is still little knowledge about the conformational features that are ideal to achieve highly reactive and stereoselective peptidic catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings by Jacobsen and co-workers also underscore that a small-molecule catalyst may interact with multiple states along a complex reaction coordinate. 15,16…”
Section: Introductionmentioning
confidence: 99%